Pengaruh Kualitas Produk, Promosi, Dan Saluran Distribusi Terhadap Keputusan Pembelian Konsumen (Studi Pada Pabrik Keripik Pisang “Metro Snack” Kota Metro) - Imron, Muhammad Ali; Suwarto, Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2022)
THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, AND DISTRIBUTION CHANNELS ON CONSUMER PURCHASE DECISIONS (STUDY ON BANANA CRIPS FACTORY “METRO SNACK” METRO CITY)” By: Muhammad Ali Imron NPM.16610189 ABSTRACT Muhammad Ali Imron Influence of Product Quality, Promotion, and Distribution Channels on Consumer Purchase Decisions (Study on Banana Chips Factory "Metro Snack" Metro City)" Supervisor (1) H. Suwarto, S.E M.M (2) Nina lelawati, S.E., M.M Indonesia's large population is a very potential market for companies that market their products. Foreign and domestic companies are trying to establish businesses and create types of products that will be favored by consumers in Indonesia. The number of these companies creates a tight business competition This study aims to determine 1) To find out whether product quality has an effect on purchasing decisions. 2) To find out whether there is a promotion effect on purchasing decisions. 3) To find out whether there is an influence of distribution channels on purchasing decisions. 4) To find out whether product quality, promotion and distribution channels affect purchasing decisions. This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population was the consumers of the Mama Alya restaurant. The sampling technique used was accidental sampling with a total sample of 75 people. Data collection techniques using a questionnaire with a Likert scale. The results showed that 1) there was a positive and significant influence between product quality on purchasing decisions. 2) there is a positive and significant influence between promotions on purchasing decisions. 3) there is a positive and significant influence between distribution channels on purchasing decisions. 4) there is a positive and significant influence between product quality, promotion and distribution channels on purchasing decisions. Keywords: Product Quality, Promotion, Distribution Channel, Purchasing Decision